R5 Peptide-based Biosilicification Using Methyltrimethoxysilane - Park, Jeong Chan; Kim, Do Hyeon; Kim, Chang Sup; Seo, Jeong Hyun (Biotechnology and bioprocess engineering, 2018)
We examined the performance of methyltrimethoxysilane (MTMS), a precursor of silicic acid, in the process of biosilicification induced by the R5 peptide from Cylindrotheca fusiformis . Recombinant GFP-R5 fusion protein was produced by Escherichia coli cultured at 25°C as a soluble and functional formation, but not at 37°C. MTMS-based biosilica deposits had a larger average diameter compared to tetraethyl orthosilicate (TEOS)-based deposits. Reducing phosphate concentration in the buffer system led to a decrease in the size of MTMS-based biosilica. These results provide insight into the surface modification of biosilica, and control of biosilica particle size, when using hydrophobic precursors such as MTMS.